2004
DOI: 10.1037/1524-9220.5.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Biceps and Body Image: The Relationship Between Muscularity and Self-Esteem, Depression, and Eating Disorder Symptoms.

Abstract: The present study examined body image and associated psychological traits in 154 college men. The comprehensive battery of measures included a novel computerized test of body image perception, the Somatomorphic Matrix, in which subjects could navigate through a range of body images, spanning a wide range of body fat and muscularity, to answer various questions posed by the computer. Subjects also completed paper-and-pencil instruments assessing depression, characteristics of eating disorders, self-esteem, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
382
3
37

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(448 citation statements)
references
References 47 publications
26
382
3
37
Order By: Relevance
“…As illustrated in Table 3, LIWC results revealed that Twitter users identified as exhibiting ED showed significantly higher mean scores on negative emotions in general, anxiety, anger and sadness when compared to a general sample of Twitter users. These findings are consistent with research from clinical settings where individuals with ED are more likely to exhibit negative emotional states and mental illness [39,40]. When comparing followers of Pro-Ana and Pro-Mia sites (see Table 4), mean scores on negative emotion, anxiety, anger, and sadness were significantly higher for Pro-Ana followers.…”
Section: Discussionsupporting
confidence: 79%
“…As illustrated in Table 3, LIWC results revealed that Twitter users identified as exhibiting ED showed significantly higher mean scores on negative emotions in general, anxiety, anger and sadness when compared to a general sample of Twitter users. These findings are consistent with research from clinical settings where individuals with ED are more likely to exhibit negative emotional states and mental illness [39,40]. When comparing followers of Pro-Ana and Pro-Mia sites (see Table 4), mean scores on negative emotion, anxiety, anger, and sadness were significantly higher for Pro-Ana followers.…”
Section: Discussionsupporting
confidence: 79%
“…There is clear overlap with these concepts and strategies described within this review, and AS use is commonly discussed alongside body image and eating disorders (Rohman, 2009;Olivardia et al, 2004). With patterns of dependence amongst long-term AS users (Kanayama et al, 2009), and similarities between disorders such as muscle dysmorphia and behavioural addictions (Foster et al, 2015), approaches may also be informed by the evidence on preventing addictive behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Study 2 was designed to delve further into this issue. Based on research suggesting gender differences in exercise motivations (Gillison et al, 2009;Kjelsås & Augestad, 2003), as well as differing impacts of body dissatisfaction on issues related to DFM (Olivardia, Pope, Borowiecki, & Cohane, 2004. ), we expect gender differences in the relation between exercise motivations, body dissatisfaction, and DFM.…”
Section: Studymentioning
confidence: 99%